Study The Effect of Substitution Ag on behavior of The High Temperature of YBa2Cu3-xAgxO6.5+δ Superconductor (Thamar University Journal of Natural & Applied Sciences, 2023)
Solid state reaction used to prepared the high temperature superconductor of YBa2Cu3-xAgxO6.5+δ compounds, Ag was isovalent substitution Cu for (x=0.0, 0.15, 0.25, 0.35, 0.45). Iodometric titration used to determine the oxygen content in the samples. The value of O2 was varies from sample to another .The result of titration exhibited value of δ is increasing when increasing of concentration of Ag. The samples was analyzed by x-ray diffraction(XRD) patterns has been used to determine the purity of the used materials ,calculation of the lattice constants and determination of its phase .The study shows a high purity samples with an orthorhombic single phase ,resistivity measurement by four probe technique and morphological analysis by Scanning Electron Microscopy (SEM).These parameters are the forming pressure of the pellets , the sintering temperature was 950oC for sintering time (30hours) with the flow of oxygen gas of about (1.25)L/min. The maximum Tc value was 94.2K for YBa2Cu5.5Ag0.45O6.5+δ, it is found Tc value increasing when increased x in the YBa2Cu3-xAgxO6.5+δ supercomputers.